Post-Flood Mental Health Crisis:: Neglected Consequences of Natural Disasters - Khaliq, Haseeb; Batool, Amna (Pakistan Armed Forces Medical Journal, 2025)
Floods are often put into perspective within the frame of visible destruction, such as houses and agricultural lands ruined, and damaged infrastructure. Still, the psychological damage that they cause to the victims is no less terrible and is left in them even when the water subsides. Research conducted globally has indicated that floods cause recovery booms of depression, anxiety, and post-traumatic stress disorder (PTSD) in societies that are already poor and have weak health systems. Psychological consequences of natural disasters are a crisis to be considered and be included in the disaster preparedness and disaster recovery policies. The systematic review of the consequences of flooding found a linear association with large levels of depression and PTSD particularly among individuals who were displaced or had their means of livelihood destroyed.1 Greater evidence exists on natural disasters confirming the same trends: exposure to natural disasters is a major risk of mood and anxiety disorders and the impact of disasters on mental health is also likely to be long-term over the years.2 Longitudinal support of this image includes one study, which monitored participants both prior to and following floods, and found sharp rises in distress, anxiety, and PTSD symptoms during the post-disaster period.3 It was found that the exposure to disasters enhances prevalence rates of common mental disorders across all settings, but the extent and duration of the impact varies with vulnerability factors.4 However, interventions remain a few. A meta-analysis of prevention strategies found very little evidence of support of psychosocial interventions in the aftermath of natural hazards and stated that there was much to be desired on scalable mental health responses to the flood-affected population.5